Analysis of the Relationship between Knowledge Level and the Use of Traditional Medicine in Sungai Rutas Village - Rusida, Esty Restiana; Chandra, M. Andi; Maulida, Siti Rahmah; Akbar, Depy Oktapian; Rakhmatullah, Aditya Noviadi (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2024)
Traditional medicines are widely used by people from the herbal medicine group, standardized herbal medicines and phytopharmaca. People know that traditional medicine is limited to herbal medicine and standardized herbal medicine. while phytopharmaca still sounds unfamiliar to the public. Regarding knowledge and use of medicines that are beneficial for health in traditional medicine, it is still limited, the majority of people consume traditional herbal medicines as many as 100 people, which they make themselves using nutritious plants. The aim of the research was to determine the relationship between knowledge and the use of traditional medicine in Sungai Rutas Village. Analytical observation research method with a cross sectional approach. The sampling technique uses non-probability sampling containing 100 samples. The results of the research show that the level of knowledge of the majority of people is sufficient, as many as 54 people (54%), and the majority of people's use of traditional medicine is sufficient, as many as 45 people (45%). Apart from that, the results of relevant statistical analysis, namely the chi-square test, found that there was a relationship between knowledge (p-value = 0.008) and the use of traditional medicine as alternative medicine in the community in Sungai Rutas Village, Tapin Regency. The conclusion was that the level of public knowledge regarding the use of traditional medicine was sufficient knowledge, namely 54 people (54%). 46 people (46%) used traditional medicine. The conclusion in this study is that there is a relationship between the level of knowledge and compliance with a p-value = 0.008.